READING CULTURE (Web of Teachers: Inderscience Research, 2024)
Elevating literacy is an important guarantee of achieving our great goals. "People stop thinking when they stop reading," said danny Didra, a renowned French philosopher. Today, young people are uniting around books in response to the high regard for the development of literacy in our country at the level of government policy. Under the leadership of our President, Shavkat Mirziyoyev, the promotion of reading is evident in the joy of young people who have taken books in the hands of their efforts to promote culture of reading and information in young people, to promote classical and modern works of Uzbek and world literature. (Matthew 24:14; 28:19, 20) After all, an important factor in improving the spirituality of the younger generation is that the emphasis on children's reading remains a symbol of confidence in our bright morning. After all, this process requires interest in reading books, regularly getting acquainted with new publications, encouraging you to learn specialized knowledge of additional publications, and acquiring competencies related to the use of library and information sources. (Matthew 24:14; 28:19, 20) Jehovah's Witnesses would be pleased to discuss these answers with you. (Matthew 24:14; 28:19, 20) It is no secret that at the moment, students are being given more global networking opportunities and are being excluded from the artifact. (Matthew 24:14; 28:19, 20) In such a situation, it is only natural to serve the effectiveness of literary education